Cutaneous zygomycosis due to Saksenaea vasiformis in an immunocompetent host - Baradkar V; Kumar S (Wolters Kluwer Medknow Publications, 2009)
Saksenaea vasiformis is an emerging zygomycete species, most often associated with cutaneous, subcutaneous and rhino- orbito-cerebral infections. Herein, we report a case of cutaneous zygomycosis of face caused by Saksenaea vasiformis in a 54-year-old immunocompetent female. The diagnosis was carried out by microscopy using KOH mount, Gram staining, Gomori′s methenamine silver staining, hemotoxylin and eosin staining and culture on Sabouraud′s Dextrose agar without actidione. Slide cultures were put up on Czapek Dox agar, which showed typical flask-shaped sporangium with rhizoids. The patient was treated successfully with intravenous amphotericin B.